Koncepcje Édouarda Séguina i ich znaczenie dla rozwoju pedagogiki osób niepełnosprawnych intelektualnie - Fetzki, Tomasz (My University, 2011)
Praca ma charakter interdyscyplinarny, historyczno – pedagogiczny. Jej celem była próba stworzenia pierwszej w języku polskim monografii Édouarda Séguina – twórcy pedagogiki osób niepełnosprawnych intelektualnie, zawierającej w miarę pełną biografię Édouarda Séguina, ukazującą jego postać wielowymiarowo, na tle różnych prądów naukowych i społecznych epoki, w której żył, jak też prezentującej w sposób w miarę całościowy oryginalność jego koncepcji pedagogicznych. Ponadto praca prezentuje wpływ, jaki koncepcje Séguina wywarły na rozwój światowej oraz polskiej pedagogiki specjalnej, przy czym specjalną uwagę poświęcono inspiracjom seguiniańskim, obecnym w twórczości takich pedagogów, jak Maria Montessori, Owidiusz Decroly, Maria Grzegorzewska i Michał Wawrzynowski.

The dissertation is of interdisciplinary, historical-pedagogical nature. Its aim was an attempt to create the first in the Polish language monograph of Édouard Séguin, the author of the pedagogy of intellectually disabled people, including a pretty full biography of Édouard Séguin, showing his personality in a multidimensional manner in the setting of various scientific and social trends of his epoch, and presenting to the largest possible extent the originality of his pedagogical concepts. Moreover, the paper presents the influence which Séguin's concepts exerted upon the development of the worldwide and Polish special pedagogy, and special heed has been paid to Séguinian inspirations to be found in the works of such educationists as Maria Montessori, Ovide Decroly, Maria Grzegorzewska and Michał Wawrzynowski.
Concepts of Édouard Séguin and their significance for the development of pedagogy of intellectually disabled people
Wydział Studiów Edukacyjnych: Zakład Historii Wychowania
Keywords: Édouard Séguin; Historia wychowania; History of education; Pedagogika osób niepełnosprawnych intelektualnie; Pedagogy of intellectually disabled people